Cuestión indígena en la América independiente - Jancsó, Katalin (Acta Hispanica, 2011)
The aim of this study is to present the political, economic and social circumstances that had an influence on the situation of Latin-American indigenous people after the wars of independence of the first decades of the nineteenth century. It describes what movements have risen during the last two centuries, what kinds of ideobgies were born to solve the indigenous problem and how the first private indigenous associations were established. It also examines the appearance of the institutionalization of indigenismo into official government policies and gives a brief view of the present legal regulation of the question in the region.